KINERJA TRANSFER PENGETAHUAN DI SEKTOR PUBLIK (Penelitian Empirik Di Politeknik Kesehatan Kementerian Kesehatan Semarang) - Darmasanti, Darmasanti (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2013)
The knowledge transfer issues in a public organization face uncommon challenges. Public organization is type of organization with complex hierarchy and bureaucracy that makes it difficult to transfer knowledge. Some people reluctant to transfer knowledge because they kept their knowledge for themselves when they had gotten promoted. This is a matter of power paradigm. Based on these reason, this study is expected to be able to answer the research problem; that is how to improve the performance of knowledge transfer in public sector.The sampling technique used in this study is purposive sampling method. This manner takes the sample with specific set of criteria i.e. education staff in polytechnic of health ofministry of public health, Semarang who are minimal in level III. The analysis techniqueused to interpreting and analyzing data in this research is Structural Equation Model (SEM)technique. The data analysis process will explain the causality relationship between variables developed in the research model.From the result of the data processing shows that the causal variable of human resource management proved to have positive and significant effects on quality of knowledge asset, variable of information technology competency and communication proved to have positive and significant effects on quality of knowledge asset, variable of quality of knowledge asset proved to have positive and significant effects on the performance of knowledge transfer, variable of human resource management proved to have positive and significant effects on the performance of knowledge transfer, variable of information technology competency and communication proved to have positive and significant effects onÂ Â the performance of knowledge transfer.